Classroom Management Strategies in Creating an Effective Learning Atmosphere - Nila Frischa Panzola; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to provide knowledge regarding the definition of classroom management, the objectives of classroom management, the function of carrying out classroom management, a wat of carrying out classroom management and how teachers stimulate classroom management. The method used in this research is library research. Library research is research carried out using library documents,including books, notes and existing works of scientists. The research achievements show that learning activities through good relationships between students and teachers, students and each other, teaching staff have the highest level in creating social conditions in learning that are suitable for studens. Therefore, teachers must carry out classroom management in order to create adequate learning conditions for students and achieve material appropriately and appropriately.